Effect of rapid solidification aluminum alloys with different Si content on mechanical properties and microstructure (Metallurgy and Foundry Engineering, 2017)
Rapid solidification is a relatively new and effective way of ultrafine grained UFG aluminum alloys production with enhanced mechanical properties. Due to significant cooling rate close to almost 106 K/s it is possible to obtain material with grain size far below 100 nm. In the present study RS aluminum alloys with Si content in a range of 5-10 wt.% were produced during melt spinning. As a result, materials in a form of ribbons were produced. As-received flakes were subjected to cold pressing into a cylindrical billets with diameter of 40 mm. Hot extrusion of pre-compacted material was subsequently performed at the temperature of 450 °C with press ram speed of 3 mm/s and extrusion ratio of λ=25. In this work influence of brittle phases on mechanical properties of as-extruded rods will be examined. Both tensile and microhardness tests were performed in order to determine mechanical properties of obtained profiles. It has been showed that brittle phases refinement during melt spinning significantly influences mechanical properties of tested materials.